Angiotensin-I-converting enzyme inhibitory peptides from eel (Anguilla japonica) bone collagen: preparation, identification, molecular docking, and protective function on HUVECs - Xiang, Huan; Huang, Hui; Shao, Yanqiu; Hao, Shuxian; Li, Laihao; Wei, Ya; Chen, Shengjun; Zhao, Yongqiang (Frontiers in Nutrition, 2024)
The objective of this study is to quickly identify the peptides that inhibit the angiotensin-I-converting enzyme (ACE) from eel (Anguilla Japonica) bone collagen hydrolysates (EBCHs) using a combination of peptidomics and molecular docking.Eel (Anguilla Japonica) bone collagen was hydrolyzed by alcalase and the hydrolysate was separated into three fractions, among which the F2 displayed a higher level of ACE inhibitory activity. According to molecular docking calculations, a total of 615 peptides were identified through nano-HPLC-MS/MS, with the prediction of seven newly discovered ACE inhibitory peptides (PMGPR, GPMGPR, GPAGPR, GPPGPPGL, GGPGPSGPR, GPIGPPGPR, GPSGAPGPR). Notably, GPPGPPGL had the lowest IC50 value of 535.84 μM among the identified peptides, indicating its potency as an ACE inhibitor. The ACE S2 pocket formed hydrogen and hydrophobic interactions with GPPGPPGL. Lineweaver-Burk plots revealed that GPPGPPGL competitively bound to ACE's active site residues. Treatment with GPPGPPGL significantly increased nitric oxide secretion (p < 0.01) and decreased endothelin-1 (ET-1) production in HUVECs. Our findings suggest that combining peptidomics with molecular docking is effective for rapidly screening ACE inhibitory peptides. Future studies should assess the bioavailability and in vivo activity of the identified peptide GPPGPPGL from EBCHs.